The Politics of Inversion: Carnivalesque Subversion in Nobody Killed Her - Ayesha Hanif; Dr. Sadia Irshad; Dr. Maria Farooq Mann (Journal of Management Practices, Humanities and Social Sciences, 2024)
Carnivalesque subversion operates through the inversion of entrenched hierarchies and established doctrines. It dismantles the preconceived notions of power and authority. The present study employs Bakhtin’s theory of carnivalesque founded in Rabelais and His World (1984) to unravel and dismantle entrenched paternalistic and political power hierarchies through the textual analysis of Javeri’s (2017) Nobody Killed Her. Addressing the research void, the present study has employed both grotesque realism and laughter simultaneously to unfurl the embedded marginalization within these potent authoritative dynamics. While contemporary academic corpus has exhaustively investigated the carnivalesque grotesque and its subversive potency, a considerable gap exists in the scrutiny of how the fusion of grotesque realism and laughter within this paradigm can function as a revolutionary strategy for challenging enrooted power hierarchies and unveiling marginalized voices. Preceding studies often deliberate on either the carnivalesque or grotesque features individually, leaving uncharted grounds regarding their collaborative effect, specifically in the backdrop of revealing and challenging patriarchy and marginalization. The present research is remarkable in its holistic perspective of the carnivalesque grotesque by applying the lens of grotesque realism and laughter simultaneously. By integrating these features, this study, through the textual analysis, strives to unearth the nuanced strategies in which laughter, as a subversive instrument within the carnivalesque grotesque, accentuates the intensity of grotesque realism in revealing power hierarchies. Moreover, the study peculiarly situates the carnivalesque grotesque as an active space where peripheral voices not only defy but dynamically reconstruct power mechanics through deliberate strategies of subversion and laughter. In this way, this research bridges an extant gap in the literature by furnishing the interplay between grotesque realism and laughter and affirms the collective potential of the carnivalesque grotesque for a radical social critique. This exploration utilizes carnivalinspired imagery to transcend and subvert conventional borders. By plummeting into the varied features of the carnivalesque grotesque, this study seeks to articulate its inherent potential as transformative agents, orchestrating a discourse that dismantles societal norms and inverses power politics.